Effects of spatial variability and correlation in stochastic discontinuum analysis of unreinforced masonry walls. (27th June 2022) - Gonen, Semih; Pulatsu, Bora; Erdogmus, Ece; Lourenço, Paulo B.; Soyoz, Serdar
Highlights: A fast and accurate modeling strategy using DEM. Stochastic analysis considering the uncertainties in modeling parameters. Stochastic analysis taking the spatial variation of parameters into account. Effects of joint-to-joint correlation of parameters. Uncertainty propagation of joint friction angle into wall's strength. Abstract: This study investigates the influence of the uncertainty in material properties on the in-plane lateral behavior and capacity of stone masonry walls via a stochastic discontinuum analysis framework. The framework is demonstrated via the 3D numerical assessment of an unreinforced masonry (URM) wall using a stochastic analysis in the form of Monte Carlo simulations. The random parameters considered in this study are the prism compressive strength of masonry, the tensile strength of the masonry units and joints, and the friction angle for joints and units. Novel research is conducted using a fast and accurate DEM model to determine whether the spatial variability of the material properties should be taken into account. In addition, the effects of joint-to-joint correlation of modeling parameters are examined to identify if such a correlation exists. A total of 1200 stochastic discontinuum analyses for 12 different cases are carried out. The results call attention to considering the spatial variability of the modeling parameters in the stochastic analysis, as they significantly reduce the variation in the wall's strength and displacement capacity. Results also demonstrate the influence of the correlation between bed-joint parameters on the strength and failure mode of the walls. Ultimately, propagation of the uncertainty in the joint friction angle into the strength and displacement capacity of the walls is quantified.